2019
DOI: 10.1063/1.5118725
|View full text |Cite
|
Sign up to set email alerts
|

Good and bad predictions: Assessing and improving the replication of chaotic attractors by means of reservoir computing

Abstract: The prediction of complex nonlinear dynamical systems with the help of machine learning techniques has become increasingly popular. In particular, reservoir computing turned out to be a very promising approach especially for the reproduction of the long-term properties of a nonlinear system. Yet, a thorough statistical analysis of the forecast results is missing. Using the Lorenz and Rössler system we statistically analyze the quality of prediction for different parametrizations -both the exact short-term pred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…This method of evaluating forecasting ability is flawed for our purposes. Previous results have shown that a low ε 1 is not a good indicator of whether a reservoir computer has learned the climate of a system 3,4 and we also observe the same effect here. Figure 4 depicts two common ways for an RC to fail to replicate the true Lorenz attractor, shown in Fig.…”
Section: Forecasting and Evaluationsupporting
confidence: 82%
See 2 more Smart Citations
“…This method of evaluating forecasting ability is flawed for our purposes. Previous results have shown that a low ε 1 is not a good indicator of whether a reservoir computer has learned the climate of a system 3,4 and we also observe the same effect here. Figure 4 depicts two common ways for an RC to fail to replicate the true Lorenz attractor, shown in Fig.…”
Section: Forecasting and Evaluationsupporting
confidence: 82%
“…More recently, RCs were used to learn the climate of a chaotic system; 3,4 that is, it learns the long-term features of the system, such as the system's attractor. Reservoir computers have also been realized physically as networks of autonomous logic on an FPGA 5 or as optical feedback systems, 6 both of which can perform chaotic system forecasting at a very high rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, additional features such as wind power generation can be included to better understand the impact of unforeseen pertubations, which are not captured in our univariate forecast. Thirdly, many alternative forecasting methods are available, from artificial neural networks (ANN) [11] and recurrent neural networks (RNN) [35] to classical methods of time series prediction [32]. However, a fully comprehensive review of all available methods was beyond the scope of this study and will be left for the future.…”
Section: Discussionmentioning
confidence: 99%
“…The readout or output layer is the only part where the weights are trained to produce a desired output which should be closer to the target data. Researchers have also devoted to find the optimal parameters of an ESN for accurate detection of target data [13,[19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%